THE INTERPRETATION OF AGRICULTURAL WORDS IN "BABURNAMA” (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article examines the terms of agriculture in the work of Zakhiriddin Muhammad Babur in Baburnama and explains them in such works as "Dictionary of the Uzbek language" and "Explanatory dictionary of the Uzbek language", created in Afghanistan. Let's take a look at the similarities. and differences. We also pay special attention to how vocabulary related to this area is pronounced today.